Bluish Discolouration of Urine Drainage Tube and Bag in a Female Patient with Spina Bifida, Paraplegia, and Suprapubic Cystostomy. (2007) - Vaidyanathan, Subramanian; Soni, Bakul M.
Abstract : We present a female patient with spina bifida, paraplegia, suprapubic cystostomy, and chronic constipation, who became anxious when she noticed a bluish discolouration of her urine drainage system. Urine microbiology revealed growth of Providencia stuartii and Staphylococcus aureus . There were no systemic features of infection and, therefore, antibiotics were not prescribed for asymptomatic bacteriuria. This patient was advised to change the urine bag every day, and was prescribed senna to facilitate bowel evacuation. She was reassured that bluish discolouration of the urine drainage tube and bag was a transient, benign phenomenon and not indicative of any underlying pathology. Over the next 7 days, the bluish discolouration gradually faded away. Clinical characteristics of patients who are likely to develop this phenomenon and the underlying biochemical mechanism for bluish discolouration of the urine drainage system are discussed in brief.